Tourism geography critical understandings of place, space and experience - Williams, Stephen 1951 May 30- (London New York, NY Routledge, 2015)
Tourism is an intensely geographic phenomenon. It stimulates large-scale, global movements of people and forges distinctive relationships between people and the places they visit. It shapes processes of physical development and resource exploitation, while the presence of visitors forges a range of economic, social, cultural and environmental relationships that have important implications for local geographies. Tourism Geography develops a critical understanding of how different geographies of tourism are created and maintained. Drawing on both historical and contemporary perspectives, the discussion connects tourism to key geographical concepts relating to globalization, mobility, new geographies of production and consumption, and post-industrial change. Building on the success of Stephen Williams cornerstone work, the addition of Alan A. Lew as co-author has enabled an even wider breadth of research to be introduced to the volume. Featuring international case studies and supported by up-to-date data, the third edition has been fully updated and offers a comprehensive review of tourism geography around the world; it examines the different perspectives from which geographers approach this important contemporary process. This book remains the only up to date and comprehensive review of geographies of tourism and the ways in which scholars can interpret contemporary tourism processes. It provides an accessible yet thorough explanation of concepts and models which promotes an understanding of their applications and limitations. Written primarily as a student text, each chapter includes guidance for further study and summary bibliographies that form the basis for independent work. Supporting materials and additional case studies are available online.
Includes bibliographical references and index.
Keywords: Tourism; Science -- Earth Sciences -- Geography; Social Science -- Human Geography; Travel -- General